Revitalisai PLTS Off-Grid 15 kWp Desa Datah Sebagai Catu Daya Pompa Air Pedesaan - Sasmita, I.G.A.D.; Giriantari, I.G.A.D.; Kumara, I Nyoman Satya (Majalah Ilmiah Teknologi Elektro, 2019)
At present all aspects of electricity are carried out by PT. PLN (Persero) throughout Indonesia. There are still many villages in Indonesia that are dark or not yet electrified. It is recorded that up to now 2,500 villages have not yet been connected to electricity. The Ministry of Energy and Mineral Resources (ESDM) has now sought a solution so that 2,500 villages can enjoy electricity. One of them is by using renewable energy. One of them is PLTS Datah, the asset is not functioning anymore and in some parts there is damage. Asah Teben Hamlet, Datah Village has an area of ??6.74 km2 which has a fairly high population with a population of 315 family heads in 2018. With such density, the water needs of each person are more than 150 liters per day per person. With the energy generated at 10 kWp, it is expected that later the need for clean water in residential areas of around 315 families can be fulfilled. With the existing water source, it can meet the water needs of residents in Asah Teben Datah Hamlet. From the calculation results, the water price is Rp. 1,288 is cheaper than the PDAM water price of Rp. 1,500. The price of water is quite cheap and can be reached by residents. Keywords— Renewable Energy, Off-grid PV, Water Pumps, Solar Pumping, Water Distribution